Strategies for Developing Post-Disaster Economic Potential in the Relocation Area of Semeru, Lumajang Regency - Octavia, Nadia Adna; Wiyono, Nabila Eka Putri; Islamey, Jazzy Madhariza (RUAS, 2025)
Lumajang Regency is one of the disaster-prone areas, one of which is the volcanic eruption disaster. One of the catastrophic events that had a significant impact was the eruption of Mount Semeru in 2021 which caused considerable physical damage and losses. In 2022, the government relocated survivors of the Semeru eruption disaster by building housing in Sumbermujur Village, Candipuro District. The short planning and construction time seems to be the reason for the lack of consideration of the economic aspects of the affected communities and environmental management. This gap further complicates the economic recovery of survivors in the relocation area, forcing them to return to their home villages to work. For this reason, studies related to the development of economic potential and appropriate environmental management are needed to rebuild the community's economy. The descriptive method was used with observation and interview stages, descriptive analysis, and integration of components including citizens' livelihoods, mobility frequency, preferred field of work, productive age demographics, and social life. Through this study, the author's recommendations can be an input for the government and related parties in the development of disaster relocation areas, especially in terms of the economic readiness of the affected communities.